2015
DOI: 10.1159/000430945
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial Cerebral Artery Dissection of Anterior Circulation as a Cause of Convexity Subarachnoid Hemorrhage

Abstract: Background: Convexity subarachnoid hemorrhage (cSAH), defined as intrasulcal bleeding restricted to hemispheric convexities, has several etiologies: reversible cerebral vasoconstriction syndrome, cerebral amyloid angiopathy, and internal carotid artery (ICA) stenosis or occlusion. However, it remains unknown whether cerebral artery dissection causes cSAH. Methods: We retrospectively investigated patients admitted to our hospital between 2005 and 2013 with ischemic stroke or transient ischemic attack caused by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…Moreover, cSAH has been described to occur invariably on the side with acute ischemic stroke, and it is notably unusual for cSAH to occur on the opposite side of the infarct territory. To date, there have been few reports about infarction with contralateral cSAH caused by RCVS, ICA dissection, embolic stroke of undetermined source, and CAA [8–10, 15]. This paper presented two cases of acute ischemic stroke with contralateral cSAH due to ICA atherosclerotic occlusion and cardioembolic stroke, respectively.…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, cSAH has been described to occur invariably on the side with acute ischemic stroke, and it is notably unusual for cSAH to occur on the opposite side of the infarct territory. To date, there have been few reports about infarction with contralateral cSAH caused by RCVS, ICA dissection, embolic stroke of undetermined source, and CAA [8–10, 15]. This paper presented two cases of acute ischemic stroke with contralateral cSAH due to ICA atherosclerotic occlusion and cardioembolic stroke, respectively.…”
Section: Discussionmentioning
confidence: 96%
“…After review of the literature we found that the majority of cases of dissecting aneurysm of the intracranial ICA were located in the supraclinoid segment. 13,18,2124 However, our two cases illustrate the use of CTA in the early detection of the outpouch in the reformatted MPR images as the possible site of the initial transmural rupture of the dissecting aneurysm.…”
Section: Discussionmentioning
confidence: 82%
“…In our case, a convexal/subconvexal focus of blood affecting the parietal lobule was seen, which could explain why the patient developed headache, facial nerve palsy, and confusion. In various case series of cSAH, reported features have included focal and transient motor and/or sensory symptoms (42–73%), including facial nerve palsy and pronator drift [15, 16]; headache (18–65%); and confusion (9.8%) [1720]. Although cSAH by definition spares the basal cistern and Sylvian fissures (which our case does not), descriptions of cSAH have been made even when these regions are not spared [21–23].…”
Section: Discussionmentioning
confidence: 99%